1999
DOI: 10.1046/j.1440-1622.1999.01525.x
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Randomized Trial Evaluating the Haemodynamic Role of Incompetent Calf Perforating Veins

Abstract: At present, the results of this study do not support the use of routine perforator ligation during superficial surgery for uncomplicated varicose veins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
35
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 17 publications
1
35
0
3
Order By: Relevance
“…Given the small subset of patients, it would be premature to suggest that perforator vein ablation alone is effective at relieving CVI symptoms. In addition, the ability of saphenous interruption alone to lower the number, size, and pressure of perforators should always be considered before perforator-directed therapy (14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the small subset of patients, it would be premature to suggest that perforator vein ablation alone is effective at relieving CVI symptoms. In addition, the ability of saphenous interruption alone to lower the number, size, and pressure of perforators should always be considered before perforator-directed therapy (14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
“…Recommendations from the American Venous Forum and Society of Vascular Surgery (7) limit indications of perforator ablation to those in close proximity to venous stasis ulcers in patients with advanced (C5/C6) disease. Studies examining perforator vein interruption at earlier disease stages were based on highly invasive surgical treatments that overshadowed any improvement in patient quality of life (16,17). The minimally invasive nature of endothermal modalities overcomes the high morbidity of traditional surgical techniques such as subendoscopic perforator surgery (18,19), and establishing the technical feasibility and safety of perforating vein EVLA sets the stage for larger-scale studies aimed at revising treatment indications.…”
Section: Discussionmentioning
confidence: 99%
“…5 Because endovenous laser or radiofrequency ablation was accepted for the treatment of incompetent GSVs, incompetent BSVs themselves were ablated without management of IPVs in IPVs combined with incompetent GSVs, but some authors have suggested that surgery involving ligation of thigh perforators results in better outcomes, and it has been demonstrated that IPVs play a significant role in recurrence of varicosities after surgery. 5,6 It has been reported that SEPS is effective in decreasing the symptoms of chronic venous disease and rapidly healing ulcers. 15, 16 Kianifard and colleagues 17 performed a randomized clinical trial to investigate the fate of IPVs after saphenofemoral ligation and stripping of the GSV, with or without SEPS, and concluded that IPVs do not remain closed after standard varicose vein surgery and that the addition of SEPS was not associated with significant morbidity but reduced the number of IPVs.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Although clinical indications for treatment of incompetent perforator veins (IPVs) have not been defined, many previous reports have suggested that IPVs may contribute to venous hypertension and play an important role in development of chronic venous disease. [5][6][7] It is not uncommon for varicosities to arise from incompetent GSVs without evidence of saphenofemoral reflux; treatment of thigh IPVs with venous reflux into the GSV is usually performed by ablation of non-healthy GSVs, and not by directly managing directly the IPV, 5 but some authors have suggested that treatment of the thigh perforator results in a better outcome, and it has been demonstrated that IPVs play a significant role in recurrence of varicosities after treatment of saphenous veins. (SEPS) and open ligation and division of perforator vein, minimally invasive management of IPVs, known as percutaneous ablation of IPVs, has recently been introduced as a safe and efficacious alternative.…”
mentioning
confidence: 99%
See 1 more Smart Citation